PEMANFAATAN LIMBAH SEKAM PADI UNTUK PEMBUATAN BRIKET ARANG DI DESA PESANGGRAHAN KECAMATAN MONTONG GADING KABUPATEN LOMBOK TIMUR - Fahrussalam, Fahrussalam; Safitri, Nurlaila; Billyan, Qonita Mulkan; Arfianti, Eni; Ansori, Wahyu; Anastasya, Anastasya; Safitri, Nadiya; Supriani, Ade; Kahfi, Dwihan Restu Ali (Universitas Mataram, 2023)
Kuliah Kerja Nyata (KKN) is a special form of community service in higher education. In the KKN PMD activities carried out in Pesanggrahan Village, Montong Gading District, East Lombok Regency, student groups carry out various activities with the main objective of utilizing rice husk waste because of the village's excellent agricultural potential. The purpose of this KKN activity is to answer various agricultural problems in the Pesanggrahan village community. This charcoal briquette training is very useful so that the Pesanggrahan area community can continue to utilize rice husk waste into appropriate technology products, namely charcoal briquettes that can be used as an alternative fuel to replace BB. . The methods used in making briquettes are (1) utilization of rice husk waste into charcoal briquettes; (2) training in making charcoal briquettes from rice husk waste; (3) use of briquettes as fuel. The results of these socialization and training activities succeeded in providing special skills to the local community, especially the farm women who were directly involved in the production of briquettes. In addition, the KKN group also carried out various other activities such as branding Pesanggrahan coffee products, making garden plant shelves, Joben Lestari Proklim inspection activities, Posyandu activities, greening program activities, coaching and cleaning the village environment. The results of these activities show that this KKN activity is able to answer some of the problems that exist in Pesanggrahan village.